2020
DOI: 10.36547/ams.26.1.449
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of isothermal heat treatments on mechanical properties of thermo-mechanically rolled S700MC steel grade

Abstract: The effect of isothermal heat treatments (1 hour at 200, 400, 600 and 800°C) on mechanical properties of thermo-mechanically rolled S700MC steel has been investigated by extensive mechanical characterizations. Treatments at 600°C increase yield and tensile strength and decrease impact energy. Below 600°C the steel retains its bainitic structure. Precipitation kinetics simulations indicate that this secondary hardening effect arises from the nucleation of fine (Nb,Ti)C particles, indicating that the bainitic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Controlling factors for this embrittlement are grain boundary sliding and the localization of strain to the proeutectoid ferrite film along the austenite grain boundary, which is produced by the γ→α transformation. Although much research has been done, the embrittlement mechanism has not been understood completely yet [ 4 , 5 , 6 , 7 ]. Based on the results of previous research [ 34 ] where the γ→α phase transformation temperatures Ar 3 -Ar 1 (894–688 °C) were determined by Thermo-Calc software for C-Mn-Al HSLA steel, it can be believed that the above-mentioned mechanism was the cause of embrittlement in zone 3 (austenitization of 1250 °C/30 s) and zone 4 (austenitization of 1350 °C/30 s).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Controlling factors for this embrittlement are grain boundary sliding and the localization of strain to the proeutectoid ferrite film along the austenite grain boundary, which is produced by the γ→α transformation. Although much research has been done, the embrittlement mechanism has not been understood completely yet [ 4 , 5 , 6 , 7 ]. Based on the results of previous research [ 34 ] where the γ→α phase transformation temperatures Ar 3 -Ar 1 (894–688 °C) were determined by Thermo-Calc software for C-Mn-Al HSLA steel, it can be believed that the above-mentioned mechanism was the cause of embrittlement in zone 3 (austenitization of 1250 °C/30 s) and zone 4 (austenitization of 1350 °C/30 s).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the improvement of surface quality of continuously cast steels, it is important to study the hot ductility behavior of steels, considering their solidifying thermal history together with the crack formation during casting. Increasing the casting speed and strain rate during straightening can be one of the useful methods to decrease crack formation shortly after the casting zone [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Jong-Tae et al [21] found that Goss texture and γ-fiber components are weakened during grain growth. Based on previous studies, few researches had reported the microstructure and texture of thin-gauge non-oriented silicon steel during recrystallization annealing [22][23][24][25][26]. A more indepth analysis of the influence of recrystallization annealing temperatures on microstructure, texture, and magnetic properties is subsequently required.…”
Section: Introductionmentioning
confidence: 99%